2013
DOI: 10.3136/fstr.19.647
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometric Determination of Copper in Edible Oil Based on the Extraction with N,N′-bis(5-methoxy-salicylidene)-2-hydroxy-1,3-propanediamine

Abstract: A new method for the determination of copper in edible oils was suggested. The proposed method is based on the extraction of copper with N, N′-bis(5-methoxy-salicylidene)-2-hydroxy-1,3-propanediamine (5MSHP) followed by flame atomic absorption spectrometry measurement. Firstly, copper complex with 5MSHP was investigated spectrophotometrically. After the analytical properties of the complexation had been defined, optimization of the extraction conditions of copper from oils was performed using a central composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…On the other hand, Ni content of sample 13 (canned green peas) was found to be below detection limit. The obtained data showed that our findings for Ni were lower than the results reported in literature [10,19]. Additionally, the results were found comparable with the report from Türkiye and India [1,8].…”
Section: Concentration Of Target Analytes In Samplessupporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, Ni content of sample 13 (canned green peas) was found to be below detection limit. The obtained data showed that our findings for Ni were lower than the results reported in literature [10,19]. Additionally, the results were found comparable with the report from Türkiye and India [1,8].…”
Section: Concentration Of Target Analytes In Samplessupporting
confidence: 83%
“…Various sample preparation protocols have been utilized prior to element detection for food samples. Liquid-liquid extraction, dry ashing, open vessel wet digestion and closed vessel wet digestion are some of the most commonly used sample preparation procedures for various samples including edible oils, milk, food additives, dairy products, frozen and canned foods [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The results illustrated that the estimated intake of Cu, Zn, Fe, Mn, Cd, Ni, Pb, and As from daily consumption of 25 g or weekly consumption of 175 g of the investigated edible vegetable oils should pose no risk to human health. Baran et al reported a new Schiff base ( N,N ′‐bis(5‐methoxy‐salicylidene)‐2‐hydroxy‐1,3‐propanediamine) synthesized by condensation reaction of 1,3‐diamino‐2‐propanol and 2‐hydroxy‐5‐methoxy‐benzaldehyde in alcoholic media. The determination of Fe and Cu in edible oils was achieved by FAAS after extraction with the Schiff base.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…The complexation reaction between Cu(II) and N,N'-bis(5-methoxy-salicylidene)-2-hydroxy-1,3propanediamine[28] …”
mentioning
confidence: 99%